1997
DOI: 10.1016/s0022-5223(97)70097-7
|View full text |Cite
|
Sign up to set email alerts
|

Surgical excision of the sinus node in a patient with inappropriate sinus tachycardia

Abstract: Inappropriate sinus tachycardia is a rare arrhythmia occurring in otherwise healthy persons, possibly owing to increased automaticity of the sinus node or an automatic From the Departments of Cardiac and Vascular Surgery," Cardiology, b and Pathology, c

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 6 publications
2
7
0
Order By: Relevance
“…1 Despite new advances in the ablation technologies, the long-term success of catheter ablation for IST remains disappointing. [7][8][9][23][24][25][26] The present study, together with our previous study, 10 demonstrated the following findings simulating the clinical features of IST. First, stimulation of the IGN induced sinus tachycardia without concurrent hypertension or enhanced AV conduction.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…1 Despite new advances in the ablation technologies, the long-term success of catheter ablation for IST remains disappointing. [7][8][9][23][24][25][26] The present study, together with our previous study, 10 demonstrated the following findings simulating the clinical features of IST. First, stimulation of the IGN induced sinus tachycardia without concurrent hypertension or enhanced AV conduction.…”
Section: Discussionsupporting
confidence: 88%
“…Pharmacological therapy for IST has been limited by poor long‐term tolerance to the drugs and the disappointing long‐term outcome 1 . Despite new advances in the ablation technologies, the long‐term success of catheter ablation for IST remains disappointing 7–9,23–26 . The present study, together with our previous study, 10 demonstrated the following findings simulating the clinical features of IST.…”
Section: Discussionsupporting
confidence: 77%
“…If all other treatments fail, surgical excision of the sinus node can be attempted [8]. Ivabradine is a relatively new drug registered for the treatment of stable angina pectoris.…”
Section: Discussionmentioning
confidence: 99%
“…This arrhythmia is most often treated with beta-blockers. However, in resistant cases nonpharmacologic treatment such as transcatheter ablation [6][7] or even surgery [8] has been attempted. Apart from beta-blockers, other potentially effective drugs are nondihydropyridine calcium antag- Springer-Verlag 21-22/2009 wkw Treatment of inappropriate sinus tachycardia with ivabradine onists and amiodarone.…”
Section: Introductionmentioning
confidence: 99%
“…February 2001 PACE, Vol. 24 Interventional therapy for inappropriate sinus tachycardia was first described in case reports; this therapy included surgical excision of the sinus node 6,24 and ethanol injection of the sinus node artery. 25 An electrophysiological approach by total ablation or modification of sinus node function recently has raised the possibility and optimism that the sinus node could be effectively slowed or totally obliterated by radiofrequency ablation.…”
mentioning
confidence: 99%